Pengembangan Strategi Bisnis Dengan Analisis SWOT Pada Usaha Gallery Print Tentena Kecamatan Pamona Puselemba Kabupaten Poso - Mba, Marsela Gitania Elsa; Walenta, Abdi Sakti; Kawani, Fredrik Bastian (Interdisciplinary Journal (IDe), 2025)
This study aims to analyze the business strategy development of Gallery Print Tentena, Pamona Puselemba District, Poso Regency, using SWOT analysis. A descriptive qualitative approach was employed, utilizing descriptive analysis, IFAS, EFAS, and SWOT matrices. Findings reveal an IFAS score of 0.7, indicating strong internal factors like product quality and responsive service. The EFAS score of 0.35 suggests greater external opportunities, such as increased printing demand and digital marketing potential, compared to threats. Positioned in Quadrant I, Gallery Print Tentena reflects a strong and opportunity-rich business, supporting aggressive growth strategies. Key strengths include product innovation, while weaknesses like high operational costs and competitive threats require attention.